Factors predictive of an advanced stage of colorectal cancer at presentation – a bi‐national study. (10th June 2020) - Vather, R.; Petrushnko, W.; Chapman, D.; Sammour, T.; Mor, I.; Warner, R.
Abstract: Aim: Identifying elements associated with advanced colorectal cancer (CRC) stage may inform understanding of whether advanced disease is a corollary of access to healthcare or tumour biology and in turn allow the use of targeted screening and awareness programmes. The aim of this study was to identify factors that predict advanced stage of CRC at presentation in Australia and New Zealand. Method: This was a cross‐sectional registry study sourced from the prospectively maintained Binational Colorectal Cancer Audit database of Australia and New Zealand. The primary outcome was stage as defined by the TNM system with associations drawn to demographic and perioperative variables. Results: In total, 25 282 separate cancers were included. Univariate analysis found younger age, treatment at a public facility, increasing American Society of Anesthesiologists (ASA) grade, more distal tumours, and less recent year of surgery to all be associated with more advanced disease; sex and presentation at a rural vs urban hospital had no bearing on this outcome. Logistic regression identified younger age (< 60 years vs > 80 years: OR 1.96; 95% CI 1.80–2.14; P  = 0.002), treatment at a public vs private hospital (OR 1.21; 95% CI 1.14–1.28; P  < 0.001), increasing ASA grade (ASA4 vs ASA1: OR 1.37; 95% CI 1.17–1.59, P  < 0.001) and more distal tumours (mid‐low rectal vs right colon tumours: OR 1.52; 95% CI 1.41–1.64; P  < 0.001) to be independent predictors of nodal or metastatic disease at presentation. Conclusion: Younger age, increasing ASA grade, more distal tumours, and treatment at a public rather than private facility are independently associated with the presence of nodal or distant CRC metastases at diagnosis.